Les collocations verbo-nominales et la traduction - Vetulani, Grażyna (Studia Romanica Posnaniensia, 2003)
The main issue addressed in this paper is how to represent complex lexical structures in dictionaries. We focus on verb-noun type collocations. We argue in favour of the concept of lexicon-grammars as a useful, general framework to show how lexical units, simple or compound, behave within the language system. We postulate development of lexicons grouping similar collocations in families according to a central meaning (common for each such family). Lexicons of that kind are precious not only as basic tools for human translators, but also as an essential part of all kinds of software contributing to the development of Human Language Technologies.